THE INTERNAL CONFLICT TAXONOMY IN INDONESIA THAT LEADS TO PROXY WAR - Suratman, Yosua Praditya (Jurnal Pertahanan dan Bela Negara, 2017)
Abstract – The conventional threats now have been shifted into unconventional threats which is now considered as one of the biggest threats for Indonesia. Proxy war is an unconventional threat and it is happening now in Indonesia through internal conflicts. The number of internal conflicts, whether vertical and horizontal, have increased significantly since the Reformation era started, and it is believed there is a third party who has a role on that. Many countries prefer proxy war due to its efficiency reasons and it creates a great result of destruction. It is not easy for the government to forecast whether the conflicts are naturally emerged or designed by third parties. Security apparatus, therefore, must design a conflict mapping in every non-military sector. The mapping will lead us in exploring all parties who have a connection to conflicts. It must be realized that internal conflicts are influenced by many factors such as ideology, politics, economics, and social, which later will continue to proxy war threats. Proxy war, therefore, will always be chosen due to its efficiency because they will not use their own resources. The strategic position of Indonesia makes Indonesia to become an object of proxy war. Keywords : Proxy war, internal conflict, security